Uncertainties and conflicting environmental adaptation strategies in the region of the Pink Lake, Senegal = Incertitudes et stratégies litigeuses d'adaptation de l'environnement dans la région du Lac Rose, Sénégal - Papa Sow (University of Bonn, Center for Development Research (ZEF), 2012)
Between the 1970s and 1990s, decreasing rainfall and devastating droughts that hit the Sahel region have led to major environmental changes ever observed. In rural Senegal, droughts combined with deforestation caused a drastic reduction of natural resources. This has undermined the precarious livelihoods of vulnerable households who were dependent on rainfed agriculture and livestock. Facing food insecurity, people have responded with subtle strategies of income diversification and social innovation. In the Sangalkam rural community (Dakar Region), people started a business by extracting and selling salt from the Pink Lake's stretch of smooth water, initially to supplement the income of their families and afterwards to engage in a commercial production. Gradually, as the salt mine was producing its 60,000 tons per year for domestically family use and export, migration waves not only spread quickly on the site, but also tourist facilities have been developed around the immediate surroundings of the Lake. Migrants and natives, working on the site, also called 'Salt Diggers', have contributed in some way, to the creation of new social and economic spaces. Over the years, they have reshaped the social and spatial relations and have become key players in collectively managing their own immediate environment. However, some of their innovative responses to the environmental stresses are not free from conflicts and tensions. Based on empirical data collected since the late 1990s, the paper focuses on self-organization of the Salt Diggers, the social, societal and environmental uncertainties resulting from their activities, but especially on existing interventions and possible actions to protect the site.
Keywords: 330; Senegal; Pink Lake; Salt extraction; Migrants; Salt diggers; Climate adaptation; Social and societal uncertainties